The Role of Microglia in Glioblastoma - Geribaldi-Doldán, Noelia; Fernández-Ponce, Cecilia; Quiroz, Roberto Navarro; Sánchez-Gomar, Ismael; Escorcia, Lorena Gómez; Velásquez, Erika Puentes; Quiroz, Elkin Navarro (Frontiers in Oncology, 2021)
Glioblastoma(GB), the most aggressive malignant-glioma, is made up of a large-percentage of glioma-associated microglia/macrophages(GAM), suggesting that immune cells play an important role in the pathophisiology of GB. Under physiological conditions, microglia, the phagocytes of the central nervous system(CNS), are involved in various processes such as neurogenesis or axonal growth, and the progression of different conditions such as Alzheimer's disease. Through immunohistochemical studies, markers that enhance GB invasiveness have been shown to be expressed in the peritumoral area of the brain, such as Transforming-Growth-Factor-α(TGF-α), Stromal-Sell-Derived Factor-1(SDF1/CXCL12), Sphingosine-1-Phosphate(S1P) and Neurotrophic-Factor-Derived-from-the-Glial-cell-line(GDNF), contributing to the increase in tumor mass. Similarly, it has also been described 17-biomarkers that are present in hypoxic periarteriolar HSC-niches in bone-marrow and in hypoxic-periarteriolar GSC-niches in glioblastoma. Interestingly, microglia plays an important role in the microenvironment that supports GB progression, being one of the most important focal points in the study of therapeutic targets for the development of new drugs. In this review, we describe the altered signaling pathways in microglia in the context of GB. We also show how microglia interact with glioblastoma cells and the epigenetic mechanisms involved. Regarding the interactions between microglia and neurogenic niches, some authors indicate that Glioblastoma-Stem-Cells(GSC) are similar to Neural-Stem-Cells(NSC), common stem cells in the Subventricular Zone(SVZ), suggesting that this could be the origin of GB. Understanding the similarities between SVZ and the tumor microenvironment could be important to clarify some mechanisms involved in GB malignancy and to support the discovering of new therapeutic targets for the development of more effective glioblastoma treatments.